Quantifying the three‐dimensional stratigraphic expression of cyclic steps by integrating seafloor and deep‐water outcrop observations. Issue 4 (12th August 2020) - Englert, Rebecca G.; Hubbard, Stephen M.; Cartigny, Matthieu J. B.; Clare, Michael A.; Coutts, Daniel S.; Hage, Sophie; Hughes Clarke, John; Jobe, Zane; Lintern, D. Gwyn; Stacey, Cooper; Vendettuoli, Daniela
Abstract: Deep‐water deposits are important archives of Earth's history including the occurrence of powerful flow events and the transfer of large volumes of terrestrial detritus into the world's oceans. However the interpretation of depositional processes and palaeoflow conditions from the deep‐water sedimentary record has been limited due to a lack of direct observations from modern depositional systems. Recent seafloor studies have resulted in novel findings, including the presence of upslope‐migrating bedforms such as cyclic steps formed by supercritical turbidity currents that produce distinct depositional signatures. This study builds on process to product relationships for cyclic steps using modern and ancient datasets by providing sedimentological and quantitative, three‐dimensional architectural analyses of their deposits, which are required for recognition and palaeoflow interpretations of sedimentary structures in the rock record. Repeat‐bathymetric surveys from two modern environments (Squamish prodelta, Canada, and Monterey Canyon, USA) were used to examine the stratigraphic evolution connected with relatively small‐scale (average 40 to 55 m wavelengths and 1.5 to 3.0 m wave heights) upslope‐migrating bedforms interpreted to be cyclic steps within submarine channels and lobes. These results are integrated to interpret a succession of Late Cretaceous Nanaimo Group deep‐water slope deposits exposed on Gabriola Island, Canada. Similar deposit dimensions, facies and architecture are observed in all datasets, which span different turbidite‐dominated settings (prodelta, upper submarine canyon and deep‐water slope) and timescales (days, years or thousands of years). Bedform deposits are typically tens of metres long/wide, <1 m thick and make up successions of low‐angle, backstepping trough‐shaped lenses composed of massive sands/sandstones. These results support process‐based relationships for these deposits, associated with similar cyclic step bedforms formed by turbidity currents with dense basal layers under low‐aggradation conditions. Modern to ancient comparisons reveal the stratigraphic expression of globally prevalent, small‐scale, sandy upslope‐migrating bedforms on the seafloor, which can be applied to enhance palaeoenvironmental interpretations and understand long‐term preservation from ancient deep‐water deposits.